Electrophysical Nature of Defects in Silicon Caused by Implanted Platinum Atoms - Boboev, Akramjon Y.; Ergashev, Biloliddin M.; Yunusaliyev, Nuritdin Y.; Madaminjonov, Jamshidbek S. (East European Journal of Physics, 2025)
The article of this study focuses on the defects caused by the platinum (Pt) atoms implanted in the silicon (Si) with the changes of their electrophysical properties after the high temperature thermal treatments. The introduction of the platinum atom into the silicon crystal lattice creates deep-level defect centers where the sensitive electrical properties and phenomena caused by temperature changes can be observed more clearly than in intrinsic defects. Of particular focus on platinum atoms incorporation, extensive studies have demonstrated significant changes of the defect structure in silicon and substantial transformation of its electrophysical properties related to the electrical conduction mechanisms and carrier scattering phenomena. Exclusive electrophysical effects were observed for platinum-doped silicon samples, which underwent high-temperature thermal annealing at 1050 °C and 1150 °C, primarily associated with the clustering of boron and platinum atoms, and the formation of complex defect aggregates. These thermal treatments enhance the interaction of isolated defects leading to the formation of clusters and complex defect entities, which greatly enhances the scattering mechanisms. These interactive effects of defects were found to be dominant in changing charge carrier transport and recombination processes in silicon crystals. Furthermore, experimental results showed a combination of scattering mechanisms that includes neutral defects, deep energy levels induced by platinum impurities, and their respective charged states. Platinum-induced defects thus enable multiple scattering mechanisms, and such hybrid mechanisms play a critical role in a silicon electrical and electronic behaviors, which influence the semiconductor applicability of the materials in high-temperature or high-performance, etc.